Level sets for retinal vasculature segmentation using seeds from ridges and edges from phase maps - Dizdaro, B.; Ataer-Cansizoglu, E.; Kalpathy-Cramer, J.; Keck, K.; Chiang, M. F.; Erdogmus, D. (2012 IEEE International Workshop on Machine Learning for Signal Processing, 2012)
In this paper, we present a novel modification to level set based automatic retinal vasculature segmentation approaches. The method introduces ridge sample extraction for sampling the vasculature centerline and phase map based edge detection for accurate region boundary detection. Segmenting the vasculature in fundus images has been generally challenging for level set methods employing classical edge-detection methodologies. Furthermore, initialization with seed points determined by sampling vessel centerlines using ridge identification makes the method completely automated. The resulting algorithm is able to segment vasculature in fundus imagery accurately and automatically. Quantitative results supplemented with visual ones support this observation. The methodology could be applied to the broader class of vessel segmentation problems encountered in medical image analytics.